The Naphthoquinone Diospyrin Is an Inhibitor of DNA Gyrase with a Novel Mechanism of Action - Karkare, Shantanu (American Society for Biochemistry and Molecular Biology, 2013)
Tuberculosis and other bacterial diseases represent a significant threat to human health. The DNA topoisomerases are excellent targets for chemotherapy, and DNA gyrase in particular is a well-validated target for antibacterial agents. Naphthoquinones (e.g. diospyrin and 7-methyljuglone) have been shown to have therapeutic potential, particularly against Mycobacterium tuberculosis. We have found that these compounds are inhibitors of the supercoiling reaction catalyzed by M. tuberculosis gyrase and other gyrases. Our evidence strongly suggests that the compounds bind to the N-terminal domain of GyrB, which contains the ATPase active site, but are not competitive inhibitors of the ATPase reaction. We propose that naphthoquinones bind to GyrB at a novel site close to the ATPase site. This novel mode of action could be exploited to develop new antibacterial agents.